Fractures of the scapular neck: diagnosis, classifications and treatment - Bartoníček, Jan; Tuček, Michal; Frič, Vladimír; Obruba, Petr (International orthopaedics, 2014)
PURPOSE: Fractures of the scapular, or glenoid, neck are strongly debated in the relevant literature. Analysis of the respective studies, however, revealed a considerable confusion in terms of definition, terminology and diagnosis. In addition, there are few studies, primarily case reviews, dealing in detail with these fractures. The aim of this article is to present detailed information about fractures of the scapular neck, based on the analysis of our own experience and of the published literature. MATERIAL AND METHODS: Our group of 17 fractures of the scapular neck comprised 14 men and three women, with a mean age of 38 years (range, 24-55). The authors diagnosed four fractures of the anatomical neck, nine fractures of the surgical neck and five trans-spinous fractures of the neck. Of these 17 scapular neck fractures, six fractures were treated non-operatively, and 11 fractures were operated on via the posterior Judet approach. The mean follow-up was 4.9 years (range, 1-11). RESULTS: Fractures in all six non-operatively treated patients healed without complications in the anatomical position and with full function of the shoulder. In 11 operatively treated patients, all fractures of the scapula and clavicle healed within three months. In nine cases the function of the shoulder was subjectively and objectively assessed as normal, and in the remaining two cases as fair. CONCLUSION: The term "scapular, or glenoid, neck" covers three different types of fractures, i.e., fracture of the anatomical neck, fracture of the surgical neck and trans-spinous neck fracture. Fractures of the surgical neck are divided into stable, fractures with rotational instability and fully unstable fractures, depending on the integrity of the coracocacromial and coracoclavicular ligaments. Accurate diagnosis of fractures of the scapular neck requires 3D CT reconstructions. Undisplaced or minimally displaced fractures may be treated non-operatively, markedly displaced fractures constitute an indication for osteosynthesis via the Judet approach.
Keywords: fraktury kostí; dospělí; radiografie; mladý dospělý; Adult; lidé; Middle Aged; Scapula; Humans; Male; Young Adult; mužské pohlaví; lopatka; Fractures, Bone; Radiography; lidé středního věku; ženské pohlaví; Female